Tanggung Jawab Hukum Notaris/PPAT Dalam Pembuatan Akta Jual Beli Yang Dipersengketakan: Analisis Putusan Nomor 26/Pdt.G/2024/Pn Gto - Ramadhani, Mutiara Putri (Fakultas Hukum Universitas Islam Batik Surakarta, 2026)
Disputes concerning the validity of Sale and Purchase Deeds (Akta Jual Beli/AJB) frequently arise in Indonesian land law practice, particularly when such deeds are alleged to have been executed without adequate explanation or without the genuine consent of the parties. This study examines the legal liability of Notaries/Land Deed Officials (PPAT) in the preparation of an AJB that later became the subject of litigation, focusing on District Court Decision Number 26/Pdt.G/2024/PN Gto and the subsequent appellate and cassation decisions. Employing a normative juridical method with statute, case, and conceptual approaches, this study analyzes the extent to which a Notary/PPAT bears responsibility for procedural compliance during the execution of an authentic deed. The findings reveal that the formal duties of Notaries/PPAT—such as reading the deed aloud, providing a comprehensive explanation of its content, and verifying the identity and intent of the parties—are crucial in determining the validity of an authentic deed. In the examined case, although the Plaintiff alleged defects of will and procedural irregularities in the AJB, the High Court and the Supreme Court did not assess the substantive liability of the Notary/PPAT. This occurred because the lawsuit was deemed formally defective due to the absence of a necessary party, namely the bank holding the mortgage over the disputed property. Consequently, the Notary/PPAT’s liability could not be judicially examined, creating a significant legal gap in the protection of parties who may be adversely affected by such transactions. This research underscores the importance of due diligence and the verification of party intent by Notaries/PPAT, as well as the need for procedural reforms in land dispute litigation in Indonesia.